2017
DOI: 10.18280/ijht.35sp0162
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of the indoor microclimate in hospital environments a case study the Papardo hospital in Messina

Abstract: The Italian hospitals are housed in old buildings, some statistics report refers which they have should be about of fifty years old. Recently new structures were built, but the trend is that over restructure and/or redevelop existing buildings, making by a cost-benefit analysis that supports this choice. The Italian construction industry covers the most part of the national energy requirements, and the hospital have a big energy request because the buildings of different areas with different destinations repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The importance of design characteristics for adequate IAQ assurance is well established [24,47,48]. Nevertheless, there are still improvement opportunities regarding the choices of products and construction materials [10,26,49,50], as well as of daily activities' products [5,48,51,52]; special attention needs to be given to engineering procedures and maintenance activities [5,25,36,[53][54][55].…”
Section: 13 X For Peer Review 7 Of 19mentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of design characteristics for adequate IAQ assurance is well established [24,47,48]. Nevertheless, there are still improvement opportunities regarding the choices of products and construction materials [10,26,49,50], as well as of daily activities' products [5,48,51,52]; special attention needs to be given to engineering procedures and maintenance activities [5,25,36,[53][54][55].…”
Section: 13 X For Peer Review 7 Of 19mentioning
confidence: 99%
“…There is also a recognized difficulty in conciliating strategies to address different indoor air pollutants occurring simultaneously [22]-recent concern has arisen regarding the formation of secondary indoor pollutants from the reaction between primary pollutants and/or other compounds present indoors or introduced by ventilation [23]. There is an increasing research interest in the design and rehabilitation of healthcare infrastructures, given the influence of construction and finishing materials in IAQ [9,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Morgenstern et al (2016) studied electricity consumption data in 28 departments across eight medium-to-large general acute hospitals in England and confirmed that different departments have considerably nonhomogeneous electricity consumption characteristics [13]. Studies in [14][15][16][17] provided an estimation of the energy requirements in healthcare facilities by considering basic services such as lighting and heating, ventilation, and air conditioning (HVAC) equipment, and medical and laboratory equipment in non-critical, non-secured, and secured categories. They also reviewed different energy-production and energy-storage technologies for healthcare systems.…”
Section: Energy Consumption In Us Healthcare Facilitiesmentioning
confidence: 99%
“…The use of smart technologies "e-sensors" in the field of environmental monitoring, in residential buildings [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], hospitals and in the field of the historical buildings under protection and safeguard, will make achieve significant developments in the "smart city" and "smart islands", encouraging the growth of tourism and quality of life. The use of renewable energy in the new technologies and plant systems [30][31][32][33][34][35], will make a significant contribution to the sustainable development of Smarts Islands.…”
Section: S91mentioning
confidence: 99%